Pembuatan Cheese Stick dari Substitusi Tepung Tapioka Dengan Tepung Jagung - Adimarta, Trian (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2022)
This study aims to determine the value of moisture content and ash content, as well as determine the organoleptic test on cheese stick products with the addition of corn flour. The method used in this study was mixing all the ingredients, 25%, 50%, 75% tapioca flour and 75%, 50%, 25% corn flour, kneading the dough, milled until thin, cut, and fried. Furthermore, organoleptic tests were carried out, namely preferences for taste, color, and texture, while chemical tests used the parameters of moisture content and ash content. The results of the organoleptic test of cheese sticks with the addition of corn flour were for a sample of 25% tapioca flour: 75% corn flour the average values ​​for taste, color and texture were 6.3, 6.3 and 7.4, for a sample of 50 % tapioca flour: 50% corn flour the average values ​​for taste, color and texture preferences were 7.7, 7.2 and 7.6 respectively, while for the sample 75% tapioca flour: 25% corn flour the average value there are preferences for taste, color and texture respectively 7.3, 6.97 and 6.4. The best results of the three treatments were cheese sticks with 50% tapioca flour: 50% corn flour. Then the results of chemical analysis of the 3 treatments showed that the cheese sticks had a moisture content value of 7.27%, 6.98% and 9.23%, respectively. Meanwhile, the ash content of the 3 treatments was 1.425%, 1.445% and 1.255%, respectively.